The Use of Salmonella Typhim Vaccine to Diagnose Antibody Deficiency - Bausch-Jurken, Mary T.; Verbsky, James W.; Gonzaga, Katherine A.; Elms, Nancy P.; Hintermeyer, Mary K.; Gauld, Stephen B.; Routes, John M. (Journal of clinical immunology, 2017)
Purpose The specific antibody response to the unconjugated 23-valent pneumococcal polysaccharide vaccine is one of the most common tests used to assess for possible humoral immunodeficiency. The results can be difficult to interpret because most people have been immunized with one or more of the pneumococcal vaccines and there is controversy regarding what constitutes a normal response. To circumvent this problem, we developed an ELISA to measure IgG-specific antibodies to the Salmonella Vi Typhim (S. Typhim) vaccine, a pure polysaccharide vaccine, which is a neoantigen for the vast majority of people in the USA. Methods We compared the pre- and post-vaccination serum titers to the Vi Typhim vaccine in healthy controls ( n = 22), patients previously diagnosed with a primary immunodeficiency ( n = 30), and patients referred for possible humoral immune deficiency ( n = 29). We also determined if the S. Typhim vaccine could be used to assess specific antibody responses in people on antibody replacement therapy. Results Following immunization with the S. Typhim vaccine, we found that a 2-fold increase in titers is 100% sensitive and specific in detecting known humoral immune deficiencies as determined by ROC curve analysis. This cut-off value was successfully applied to possible immune deficiency patients ( n = 29), resulting in the diagnosis of seven subjects with humoral immunodeficiency. The use of immunoglobulin replacement therapy did not affect the median response ratios compared to subjects not receiving gammaglobulin. Conclusion This study suggests that measurement of the specific antibody response to the S. Typhim vaccine may have advantages over pneumococcal vaccination in the evaluation of the humoral immune response.